The Effect of Non-Performing Financing, Financing to Deposit Ratio, and Capital Adequacy Ratio on Murabahah Financing at Bank Mega Syariah for the 2019-2025 Period - Nelly Himmatus Sa’diyah; Kus Irawan Prabowo (Journal of Economics and Social Sciences (JESS), 2026)
This research is motivated by the phenomenon of fluctuations in murabahah financing occurring at Bank Mega Syariah. Murabahah financing is one of the financing products that is quite dominant used in Sharia Commercial Banks At Bank Mega Syariah, murabahah financing is also quite dominant. Murabahah financing at this bank tends to decline starting at the end of 2019, where murabahah financing dropped drastically in 2020. However, it increased again in 2025. This condition is allegedly influenced by several internal banking factors, including Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Capital Adequacy Ratio (CAR). In the study, a quantitative approach is used, the type of research is associative. This research uses a sample in the form of quarterly financial statements of Bank Mega Syariah for the 2019–2025 period. The sampling technique uses saturated sampling, so that all populations become research samples. The data collection technique is carried out through documentation. The data that has been collected is then analyzed using the multiple linear regression analysis method through the EViews 13 application. The results of this study show that: (1) The Non-Performing Financing (NPF) variable has no effect on murabahah financing. (2) The Financing to Deposit Ratio (FDR) variable has a significant positive effect on murabahah financing. (3) The variable Capital Adequacy Ratio (CAR) has a significant negative effect on murabahah financing. (4) Simultaneously (together), the variables of NPF, FDR, and CAR have an effect on murabahah financing in Mega Syariah Bank.